2005
DOI: 10.1002/dvdy.20299
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog regulates proliferation of the retinal ciliary marginal zone in posthatch chicks

Abstract: The ciliary marginal zone (CMZ) has long been known to be a source of postembryonic neuronal production in the retinas of fish and amphibians, and more recently, birds. However, there is little known about the factors that are required for the maintenance of this neural stem cell zone. The cells of the CMZ respond to mitogens such as endothelial growth factor, insulin-like growth factor-1, and insulin, factors that are also mitogenic for embryonic retinal progenitors, suggesting that the continued expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 35 publications
3
52
1
3
Order By: Relevance
“…14 Hh activation increases the number of BrdU-positive cells in the CMZ, whereas Hh inhibition has the opposite effects. 8,11 We thus propose that Hh signaling converts the quiescent retinal stem cells of the most peripheral CMZ into the fast cycling transient amplifying progenitors that are closer to differentiation in the central CMZ (Fig. 1A and B).…”
Section: Converting Stem Cells Into Transient Amplifying Progenitors:mentioning
confidence: 95%
See 1 more Smart Citation
“…14 Hh activation increases the number of BrdU-positive cells in the CMZ, whereas Hh inhibition has the opposite effects. 8,11 We thus propose that Hh signaling converts the quiescent retinal stem cells of the most peripheral CMZ into the fast cycling transient amplifying progenitors that are closer to differentiation in the central CMZ (Fig. 1A and B).…”
Section: Converting Stem Cells Into Transient Amplifying Progenitors:mentioning
confidence: 95%
“…Results from mice and chicks showed that Shh activation increases markers of proliferation, such as incorporation of the S-phase marker 5-Bromodeoxyuridine (BrdU), suggesting that Hh stimulates proliferation. 7,8,9 In contrast, several studies of zebrafish mutants for Hh components revealed that Hh inhibition leads to prolonged retinal proliferation, suggesting that Hh directs cell cycle exit. 10 Our recent work performed both on amphibian and fish retinas reconciles these two different views by highlighting a conserved function of Hh signaling in the control of cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…51 In chick and mouse retina Shh activation resulted in increased BrdU incorporation suggesting that Hh signaling promotes proliferation. [52][53][54] However, Hh mutant Zebrafish exhibited prolonged retinal proliferation due to the inability of precursor cells to exit the cell cycle. 55 Recent work has suggested that Hh signaling may effect stem, progenitor and mature cells differently, with Hh signaling either promoting proliferation or pushing cells out of the cell cycle resulting in reduced proliferative ability depending on the state of differentiation of the cell.…”
Section: Hh Signaling Attenuates Peripheral T-cell Activation and Promentioning
confidence: 99%
“…Early posthatch chicks also house stem cells in the CB that are able to proliferate in response to injection of exogenous growth factors such as insulin, epithelial growth factor, and FGF2 (Fischer and Reh, 2003). Moshiri et al (2005) have shown that Shh signaling is important in the CMZ as it is able to stimulate proliferation in the posthatch chick eye. Interfering with the Hedgehog (Hh) pathway inhibits the ability of progenitor cells in this region to proliferate.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that both FGF2 and Shh are able to independently induce retina regeneration from the CB/CMZ in E4 chick eyes . Thus, both FGF and Shh are important in the regulation of stem/progenitor cells in the CB/CMZ of the embryonic and postnatal chick (Fischer et al, 2002;Fischer and Reh, 2003;Spence et al, 2004;Moshiri et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%